2014
DOI: 10.1194/jlr.p054163
|View full text |Cite
|
Sign up to set email alerts
|

Individual variation of human S1P1 coding sequence leads to heterogeneity in receptor function and drug interactions

Abstract: Sphingosine 1-phosphate receptor 1 (S1P 1 ) is a G protein-coupled receptor (GPCR) for a versatile lysophospholipid mediator sphingosine 1-phosphate (S1P) ( 1, 2 ). S1P levels are high in blood and lymph, but low in the interstitial tissue fl uid, thereby forming a gradient important for immune cell traffi cking ( 3 ). S1P, which is poorly soluble in aqueous solutions, is bound by specifi c chaperones. For example, plasma S1P is bound by albumin ( 4 ) or apoM ( 5 ), a specifi c apolipoprotein found in HDL. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 49 publications
0
21
0
1
Order By: Relevance
“…Recently, Obinata et al (2014) identified several single nucleotide polymorphisms in the S1PR1 gene that influence receptor function. One single nucleotide polymorphism in S1PR1 correlated with a differential coronary artery disease risk, suggesting that genetic variations of S1PR1 may be involved in the pathogenesis of CV diseases.…”
Section: S1p: New Player In Bp Regulation?mentioning
confidence: 99%
“…Recently, Obinata et al (2014) identified several single nucleotide polymorphisms in the S1PR1 gene that influence receptor function. One single nucleotide polymorphism in S1PR1 correlated with a differential coronary artery disease risk, suggesting that genetic variations of S1PR1 may be involved in the pathogenesis of CV diseases.…”
Section: S1p: New Player In Bp Regulation?mentioning
confidence: 99%
“…S1P1 is expressed in a variety of cell types, including endothelial and epithelial cells, T cells, natural killer T cells, innate lymphoid cells, and dendritic cells (26,34,35). In humans, 15 nonsynonymous S1PR1 SNPs have been identified by the U.S. National Heart, Lung, and Blood Institute Exome Sequencing Project (36). Functional variants have been associated with asthma susceptibility, constituting a risk factor for disease severity (37), which supports the idea that genetic variants of S1PR1 may influence physiological and pathological events in the lung compartment.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, significantly fewer S1PR1 missense variants were observed in gnomAD than expected (232 missense variants expected, 120 observed missense variants, z = 2.61). Finally, missense variants identified in the NHLBI Exome Sequencing Project have been functionally assessed: the Arg120Pro variant (rs149198314; identified in 1/13,005 alleles) failed to activate S1P1 signaling or internalization in response to S1P, and Arg120 was found to be critical for S1P binding [41][42][43]. Hence, individuals who are heterozygous for predicted loss-of-function S1PR1 alleles have been observed at very low frequency, and cardiomyopathy exome/genome sequencing studies may reveal additional S1PR1 variants that disrupt S1P1 function.…”
Section: Discussionmentioning
confidence: 99%